From Russia, with tactic? - Aranda, C. A.; Campos, L. M. (Journal of Human Sport & Exercise, 2018)
Russia will host the 2018 FIFA World Cup. Football has changed and new space-time concepts have emerged in recent years to help understand the performance of a football team. We need analyse football from a holistic perspective. Every team of football is understanding like a superorganism with two fundamental characteristics: division of labour and a communication system. In the future new concept, altruistic cooperation, will help know a complexity in football.